Access to Abortion in Central Appalachian States: Examining County of Residence and County‐Level Attributes. Issue 4 (20th September 2018) - O'Donnell, Jenny; Goldberg, Alisa; Betancourt, Theresa; Lieberman, Ellice
Abstract : CONTEXT: Studies of how women's individual characteristics and place of residence are related to variability in gestational age at the time of abortion have not examined county of residence and county‐level characteristics. The county level is potentially meaningful, given that county is the smallest geographic unit with policy implications . METHODS: Data on 38, 611 abortions that took place in North Carolina, Virginia and West Virginia in 2012 were used to study the relationship between gestational age and county‐level attributes (e.g., metropolitan status and poverty). Three‐level hierarchical linear models captured individuals nested in county of residence, clustered by state of residence, and adjusted for individual characteristics and distance traveled to care . RESULTS: Eight percent of the variation in gestational age at abortion was attributable to county‐level characteristics. Residents of counties characterized by persistent poverty obtained abortions 2.3 days later in gestation than those from counties not characterized by that level of economic hardship. Women living in nonmetropolitan counties obtained abortions 1.7 days later than those living in metropolitan counties, even after distance traveled and county‐level poverty were controlled for . CONCLUSION: County of residence is relevant to gestational age at the time of abortion for women in these three states. Evidence that county‐level attributes are related to access adds insight to the consequences for women when the landscape of abortion service delivery shifts. Integrating county of residence into research on access to abortion services may be critical to capturing disparities in access .